2016
DOI: 10.1103/physrevb.94.104421
|View full text |Cite
|
Sign up to set email alerts
|

Magnon-phonon coupling and two-magnon continuum in the two-dimensional triangular antiferromagnetCuCrO2

Abstract: CuCrO2 is a manifestation of a two-dimensional triangular antiferromagnet which exhibits an incommensurate noncollinear magnetic structure similar to a classical 120• ordering. Using the inelastic neutron scattering technique, direct evidence of a magnon-phonon coupling in CuCrO2 is revealed via the mixed magnon-phonon character of the excitation mode at 12.5 meV as well as a minimum at the zone boundary. A simple model Hamiltonian that incorporates an exchange-striction type magnon-phonon coupling reproduces … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 30 publications
3
17
1
Order By: Relevance
“…8-c), consistent with IXS measurements. We note that the T -dependence of the phonon intensity of ∼13 meV peak in our DOS measurements differs from the observation by Park et al [26], who reported no change in the phonon intensity at ∼13 meV above T N along [H,H,0] for 1 3 ⩽ H ⩽ 2 3 . Figure 3-(d-i) shows χ ′′ (Q, E) at low Q zooming on magnetic excitations (12 meV data).…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…8-c), consistent with IXS measurements. We note that the T -dependence of the phonon intensity of ∼13 meV peak in our DOS measurements differs from the observation by Park et al [26], who reported no change in the phonon intensity at ∼13 meV above T N along [H,H,0] for 1 3 ⩽ H ⩽ 2 3 . Figure 3-(d-i) shows χ ′′ (Q, E) at low Q zooming on magnetic excitations (12 meV data).…”
Section: Resultscontrasting
confidence: 99%
“…This unusual T -dependence of κ L in CuCrO 2 is markedly different from that in the non-magnetic analogue CuAlO 2 . Be- sides providing lattice dynamics information for a wide range of temperature, our measurements of phonon dispersions with IXS and INS also clearly distinguish between phonon and magnon intensities, which is crucial in understanding spin-phonon coupling across T N in this class of spin driven multiferrorics [25,26].…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…2, there seems to be a very diffuse intensity located at around 18 meV. This may be similar to the magneto-elastic excitations observed in (Y,Lu)MnO 3 and CuCrO 2 [7,22]; (1) the relatively strong intensity near the B and D points and (2) a similar energy transfer (18 meV) above the coherent modes. Such magnetoelastic excitations originate from a hybridization of specific phonon and magnon modes in noncollinear magnets.…”
supporting
confidence: 73%